Microstructure and surface finish influences on AA7085-T7452 small fatigue crack growth rates. (November 2022) - Main, Ben; Dixon, Ben; Jones, Michael; Barter, Simon
Highlights: Examines two factors in small fatigue crack growth in aluminium alloy 7085 – microstructure and nucleation from etch pitting due aircraft part surface coating processes. Finds AA7085 small fatigue crack growth rates, on average, are relative insensitivity to grain size. Presents evidence that etch pits from pre-anodize and pre-ion vapour deposition process steps are less effective crack nucleating discontinuities in AA7085 than AA7050. Abstract: Aluminium alloy 7085 forgings are a suitable replacement for 7050 thick-plate material in large, thick airframe parts such as bulkheads. In this paper two factors in small fatigue crack growth rates are contrasted for these two materials – microstructure and fatigue crack nucleation from etch pitting, an unavoidable artefact of aircraft production surface finishes for high strength aluminium alloys. Evidence of the complex interactions between small fatigue cracks and the microstructure of AA7085-T7452 is presented at a sub-grain level to explain scatter in small fatigue crack growth rates below 1x10 -9 m/cycle and ΔK = 1.2 MPa√m. Above this level, small fatigue crack growth rate data is presented that demonstrates that growth rates are relatively insensitive to grain size in this material. Equivalent pre-crack size data is presented for several AA7085 and AA7050 specimens, in different material directions, and treated with pre-Type 1C anodising and pre-ion vapour deposition etching processes. The measured mean depths of the etch pits produced in both materials was found to be similar yet etch pitting in AA7085 was shown to be less effective in nucleating small fatigue cracks. The etching pre-processes associated with ion vapour deposition coatings were also found to lead to more effective fatigue crack nucleation than pre-anodizing treatments.